Specific levels of calcidiol, calcitriol, cathelicidin and interferon gamma in diabetic patients with TB infection in Jakarta, Indonesia; Case control study - Yunita Arliny; Dewi Behtri Yanifitri; Budi Yanti; Diennisa Mursalin (Jurnal Respirologi Indonesia, 2021)
Vitamin D plays a role in regulating the immune system via Vitamin D receptors, expressed by T-helper cells (Th). Cathelicidin LL-37 is an antimicrobial peptide that acts as the primary barrier against the Mycobacterium tuberculosis bacterial infection, which is induced by calcitriol, the active form of Vitamin D3. Interferon gamma (IFN-γ) is a cytokine released by Th-1 cells, and is essential for the elimination of M. tuberculosis. This study aims to determine the state of, and correlation between, calcidiol, calcitriol, cathelicidin and IFN-γ levels, as well as other clinical factors among patients with Type 2 Diabetes Mellitus (T2DM) with active TB coinfection. Further analysis is also performed to study the differences between T2DM patients with active tuberculosis, latent TB and without TB infection.